Model struktural visionary leadership dalam kepemimpinan berbasis data pada Sekolah Dasar di Kabupaten Kulon Progo: Structural model of visionary Leadership in data-based leadership in Elementary Schools in Kulon Progo Regency - Dwi Yuliastuti; Didi Supriadi; Rejokirono Rejokirono (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
Visionary leadership drives the adoption and implementation of data-based policies as part of the school's organizational vision and goals. The aim of this research is to obtain a structural model of visionary leadership in data-based leadership that meets the goodness of fit model. Then find out the quantitative contribution of visionary leadership to data-based leadership. The research method uses a cross-sectional quantitative method. Survey research using a questionnaire as a data collection tool with a sample of 100 elementary school principals in Kulon Progo Regency using purposive sampling. Analysis of research data using factor analysis and structural equation modelling (SEM) using SmartPLS 3 software. The results of factor analysis show that the factors are adapting (0.896), building on image (0.877), developing organization (0.851), empowering (0.790), stimulating intellectual (0.808), supporting (0.834), and taking risk (0.941) have a significant effect on the formation of the visionary leadership construct. Likewise, the data-based leadership construct is significantly shaped by the factors digital adaptiveness ability (0.825), digital competitive ability (0.904), digital culture ability (0.845), digital drive ability (0.806), digital knowledge ability (0.883), digital literary skills (0.580), and embrace digital ability (0.600). The results of structural equation modelling testing show that Visionary Leadership has a significant impact on data-based leadership. This is supported by the estimated coefficient of 0.625 which is statistically significant at the 5% significance level. The analysis produces an R-square value of 0.390 which shows that Visionary Leadership has an influence of 39.0% on data-based leadership.